Simulation of random processes with known correlation function with the help of Karhunen-Loeve decomposition - Moklyachuk, O. (Інститут математики НАН України, 2007)
A theorem is proved that allows to use approximations for construction of the Karhunen-Loeve model of stochastic process with known correlation function.